Ischemic Stroke with Anticoagulant Protein C Deficiency - Cynthia; Diana Aulia (GoAcademica Research & Publishing, 2023)
Ischemic stroke is a circulatory disorder in brain is caused by reduced or stopped blood flow in some areas of brain. It can be caused by thrombotic lesions resulting from atherosclerosis and by emboli that have detached from the lesions atherosclerosis in the heart or cerebral arteries. Ischemic stroke category consists of emboli and lacunae. Characteristic profile clinical manifestations of acute embolic stroke are sudden onset with maximal neurologic deficits. Embolic often originate from heart or from ulcerative carotid plaques. Atrial fibrillation is a predisposing factor for cardiac thrombus, associated with six times of risk increase in strokes. The patient had a diagnosis with a clinical description of a history of post cerebrovascular disorder non hemorrhagic (CVD-NH/ischemic stroke) with hypercoagulable state from an outpatient clinic on April 13th, 2016 for examination antithrombin III (AT III), protein C, protein S, ACA IgG, ACA IgM, fibrinogen, D-dimer, and INR.